Perancangan Komik Web Tentang Kisah Perempuan Hebat Dalam Alkitab - Peyoh, Audree Graciela Salomita; Lukman, Christine Claudia; Setiawan, Hendra (Fakultas Desain Universitas Komputer Indonesia, 2024)
Nowadays, young people are increasingly able to access various information from the internet easily, both useful information and harmful information to their spirituality and personality. This can happen to younger generations of Christians who become more interested in worldly things over the internet than spiritual ones. Currently, the topic is the story of the great women in the Bible, Abigail and Esther, which deals with the issue of gender equality. This is a visualization and simplification of stories from the Bible. It requires literature study, interviews, and focus group discussions and then the data is analysed and used as a foundation in designing media, with communication concepts that use casual language and are informative, as well as creative concepts that use is Korean comic style that young people like today, with color compositions that match the story setting, and vertical comic layouts so the one who read can understand and enjoy it.